The antecedents of consumers’ attitude and its consequences on online purchase intention - Utami, Putu Diah Putri; Rahyuda, Ketut (International research journal of management, IT and social sciences, 2019)
This study aims to explain the effects of the quantity of posts, views, and reviews (QPVR) of UGC videos shared on YouTube towards its credibility as a source and the usefulness of the information it shares, as well as how it influences consumers’ attitude towards UGC that ultimately leads to their online purchase intention. The population of this research is every female consumer residing in Denpasar that has seen cosmetics video reviews on YouTube. A sample of 100 respondents was collected through online questionnaires. The data obtained were tested using PLS (Partial Least Square) analysis. The results showed that information usefulness of a UGC video had a positive and significant effect on consumers’ attitude towards UGC, thus resulting in their online purchase intention. Furthermore, it showed that QPVR had a positive and significant effect on both credibility and information usefulness of the cosmetics product content generated by users on YouTube. However, UGC’s credibility does not prove to have a significant effect on consumer’s attitude towards UGC due to lack of trust and dependability.